2005
DOI: 10.1007/s10733-005-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray Diffraction Study of γ-Irradiated Siloxane Block Copolymers

Abstract: It was found that 20 : 5 and 40 : 10 siloxane block copolymers of the general formula {( CH 3 ) 2 SiO } m {[ C 6 H 5 SiO 1.5 ] a [ C 6 H 5 SiO · ( OH )] 1 -a } n are structurally different: the 20 : 5 siloxane block copolymers consisted of 8-10 pairs of blocks, whereas the 40 : 10 siloxane block copolymers consisted of 1-2 pairs of blocks. The diffraction patterns of the initial 20 : 5 siloxane block copolymers were characterized by two reflections with 2 θ maximums at 7.7° and 12.2° , whereas the diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Structural studies on polysiloxane indicated XRD peaks located at 7.5 and 12 2 , respectively for samples containing between 8 and 10 building pairs. For samples containing only 1 to 2 building pairs only a single XRD peak centered at 21 = 8 2 was observed [19] In our study, the position and the thickness of the large XRD peak around 21 = 12 2 is dependent on the composition of the sample. The decomposition of this peak into its Gaussian components suggests the dispersion of the number of building pairs influenced by the silica content (figure 2).…”
Section: Resultsmentioning
confidence: 39%
“…Structural studies on polysiloxane indicated XRD peaks located at 7.5 and 12 2 , respectively for samples containing between 8 and 10 building pairs. For samples containing only 1 to 2 building pairs only a single XRD peak centered at 21 = 8 2 was observed [19] In our study, the position and the thickness of the large XRD peak around 21 = 12 2 is dependent on the composition of the sample. The decomposition of this peak into its Gaussian components suggests the dispersion of the number of building pairs influenced by the silica content (figure 2).…”
Section: Resultsmentioning
confidence: 39%
“…5 and 6. It can be seen, that all patterns contain a broad reections located at the 2q range of 3-30 corresponding to the amorphous polymer phase 39,40 and indicating the short-range ordering only. Aer incorporation of Pt, these reections are preserved.…”
Section: Physicochemical Properties Of Network-platinum Systemsmentioning
confidence: 93%
“…2h 5 128 (d-spacing value ca. 7.4 Å ) can be ascribed to the distance between the chains in cross-linked products, [31][32][33] and its shape indicates the amorphous nature of 34 which confirms the presence of Pt 0 . Comparison of patterns of starting compounds with those after incorporation of platinum, leads to the statement that reflections ascribed to metallic Pt are present in diffractograms of all Pt-containing systems.…”
mentioning
confidence: 85%